PENDAMPINGAN BERBASIS EDUKASI DALAM MENCEGAH BAHAYA JUDI ONLINE BAGI GENERASI PEMUDA DI PAMEKASAN - Sayyi, Ach.; Halim, Abdul; S H, Sheik Muhamed; Fajriyah, Fajriyah (ABDINA: Jurnal Sosial dan Pengabdian kepada Masyarakat, 2025)
Online gambling has emerged as a significant threat to youth in the digital era, particularly in regions with high internet penetration but low digital literacy. This community service program was conducted among the Salo’lo’ Youth Generation (Generasi Pemuda Salo’lo’/GPS) in Lawangan Daya Subdistrict, Pamekasan, aiming to enhance knowledge, digital skills, and critical awareness regarding the dangers of online gambling. The methods employed included interactive counseling sessions, group discussions, educational video screenings, digital literacy training, and simulations on identifying and reporting harmful content. Evaluation was carried out using pre- and post-tests as well as participant observation. The results revealed a substantial increase in participants’ understanding of various forms, patterns, and impacts of online gambling 90% of participants were able to identify types of digital gambling, 88% understood its psychological, social, and economic consequences, and 85% grasped its legal and religious implications. Participants' digital competence also improved, with 87% successfully distinguishing between legal and illegal sites and 82% capable of reporting harmful content through official channels. The active participation rate reached 92%, and the program produced additional outcomes, such as the formation of the Anti-Online Gambling Task Force (Kelompok Kerja Anti Judi Online/KKAJO) and the dissemination of digital campaign materials. These findings suggest that community-based educational approaches, reinforced by local cultural values, are effective in fostering youth resilience against the growing menace of online gambling.